Effects of palladium on the optical and hydrogen sensing characteristics of Pd-doped ZnO nanoparticles - Anh-Thu Thi Do (Beilstein Journal of Nanotechnology, 2014)
The effect of palladium doping of zinc oxide nanoparticles on the photoluminescence (PL) properties and hydrogen sensing characteristics of gas sensors is investigated. The PL intensity shows that the carrier dynamics coincides with the buildup of the Pd-related green emission. The comparison between the deep level emission and the gas sensing response characteristics allows us to suggest that the dissociation of hydrogen takes place at PdZn-vacancies ([Pd 2+(4d9)]). The design of this sensor allows for a continuous monitoring in the range of 0–100% LEL H2 concentration with high sensitivity and selectivity.